การปรับปรุงผลิตภาพการผลิตตัวส่งสัญญาณในอุตสาหกรรมอิเล็กทรอนิกส์ - พัทธพงศ์ พรมชัย (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
In the signal sender production of a case study in electronics industry, there a problem of high wastes level which effects to low productivity and high work in process (WIP) . These two factors were critical since they influence high production cost. Therefore, the purpose for this independent study was to increase productivity and reduce WIP of the signal sender production line. At the current state, the production line had average capacity of 3,388 pcs/day. The winding process was shown to be the bottleneck process. This independent study focused on reducing non-value added activities and number of operators in order to produce the same amount of production. First, this independent study applied Motion and Time study principle and we found that the total production time of the Signal Sender was 138.4 sec/pc and 63% of production time was the non values added activities. Second, the improvement techniques which were ECRS and Line balancing were applied to reduce the waste in production line. Finally, the one piece flow concept was adopted to reduce WIP in the production line. After the improvement techniques were implemented, the result showed that the independent study can achieve the research objective by increasing productivity from 242 pcs/person/day to 423 pcs/person/day or 75%. Moreover, WIP decreased from 199 pcs to 141 pcs or 29%.